Measuring the effectiveness of border crossing management between Malaysia & Thailand with reference to Bukit Kayu Hitam – Sadao and Padang Besar – Padangbasa - Muhammad Hatta, Kassim (2023)
The Immigration Department of Malaysia, being the first line of defence, has always been in the limelight for its success stories as well as its flops due to integrity, system, and management issues. The debatable issue in Integrated Border Crossing Management (IBM) is the difficulty for any immigration operator to maintain balance with compliance requirements. Thus, the department needs to keep in line with the fast-emerging threats by having proper planning to keep the department strong in the challenging emigrational environment. An IBM system commonly refers to the number of agencies manning multiple authorizations in border crossing examinations that involve the examination of people and goods. Most of the previous research have limited studies and limited data on the topic. Bukit Kayu Hitam and Padang Besar have traditionally operated to accommodate the locals and have expanded to be among the most challenging entry points due to their accessibility to multiple irregular activities. Thus, the aim of this research is to study the current implementation of the border crossing management system in managing the border between Malaysia and Thailand. Moreover, to suggest countermeasures to reduce the implementation gaps in managing the border between both countries, as the increasing gaps may lead to management issues. The research was conducted using a qualitative method (semi-structured interviews and ATLAS.ti 22 software), with results indicating that three major themes emerged which are Policy, current technology adoption, and border crossing management are factors that influence cross-border management. This illustrates the importance of having an efficient control module that reflects the smoothness of the border crossing process while maintaining national security and providing a decent examination experience to attract potential investors or business opportunities for Malaysia. Theories applied in the research significantly were beneficial in concluding the scope of research on cross border management at the location of research.